Efficacy and Safety of 5-Fluorouracil Cisplatin in Comparison with Gefitinib in Advanced and Recurrent Head and Neck Cancer - Tooba Imtiaz Baqai, Ghulam Haider, Javeria Anzar, Sana Sehar, Nargis Aalam Abro, Aamera Shah, Reeta Kumari, Salar Haider, Kiran Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The present study aimed to evaluate the efficacy and safety of Cisplatin plus 5-Fluorouracil in comparison with Gefitinib in advanced and recurrent head and neck cancer. Methods: A quasi experimental study was undertaken at the Department of Oncology, Jinnah Postgraduate Medical Centre between 2nd April 2022 and 2nd December 2022. All patients with histologically confirmed new or recurrent cases of head and neck cancer in the advanced clinical stage were recruited. Demographic data (age, gender, body mass index, comorbidity, etc.), medical history and clinical characteristics, routine biochemical analysis, urinalysis, and tumor assessments via CT scans and MRI, adverse effects and toxicity were recorded. Patients were divided randomly into two groups. Group A received Cisplatin plus 5-Fluorouracil while group B received Gefitinib monotherapy. The primary end point of the study was the overall response rate (ORR). Results: Complete response was demonstrated by seven (7.3%) and four (4.8%) individuals in Group A and B, respectively. Vomiting was significantly associated with Cisplatin plus 5-Fluorouracil with a frequency of 38 (39.58%) as compared to 10 (11.9%) in Group Gefitinib (p<0.001). Renal insufficiency was also experienced more frequently in Group A; 26 (27.1%) as compared to Group B; 2 (2.4%) (p<0.0001). Fever (p=0.004) and bone marrow suppression (p<0.001), loss of hearing (p=0.012) and skin rash (p<0.0001) were all significantly more frequently experienced by patients receiving Cisplatin plus 5-Fluorouracil as compared to those receiving Gefitinib. Conclusion: Gefitinib monotherapy was found to be more favorable for patients diagnosed with advanced head and neck cancer because oral mode of administration of Gefitinib alleviates the need for a hospital admission which makes it a more feasible option as compared to the alternatives. Furthermore, Gefitinib has a better safety profile and a relatively lower incidence of adv erse effects. Keywords: Cisplatin, Fluorouracil, Geftinib, Head Cancer, Neck Cancer, Recurrence